Pengaruh Ukuran, Struktur Hutang, dan Umur Perusahaan Terhadap Profitabilitas: Studi pada Perusahaan Makanan dan Minuman BEI 2020-2022 - Rustianawati, Mutimmah; Febrian, Sholehuddin Dwi; Suharsono, Judi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
Due to the food and beverage industry's rapid expansion, many businesses are forced to improve their performance in order to continue running efficiently. The profitability ratio, which is based on information from the income statement and balance sheet, is one of the most important ratios used to evaluate a business' success. The level of profitability also shows how well the company's assets are handled and how well they can produce earnings, which guarantees the company's long-term viability and gives investors peace of mind. This study sought to determine the most important contributing factor while examining the effects of age, debt structure, and company size on profitability alone and in combination.The goal of this study is to determine the connection between the independent and dependent variables using an associative quantitative approach. A significance of 0.099 indicates an inconsequential influence for company size, according to partial research findings. In contrast, the debt structure and the company's age have a significance of 0.000 and 0.000, respectively, indicating that they have a considerable impact. With a significance level of 0.000, or less than 0.05, the factors of age, debt structure, and company size all have a significant effect. The debt structure has the most significant negative impact of these three variables, with a normalized beta coefficient of -0.594.